2022
DOI: 10.5603/aa.2022.0013
|View full text |Cite
|
Sign up to set email alerts
|

Leukotrienes in the atherosclerotic cardiovascular diseases — a systematic review

Abstract: Introduction:The role of inflammation in the pathogenesis of atherosclerotic diseases is strongly suggested. There are multiple studies indicating the possibility of a pathophysiological connection between atherosclerotic changes and leukotrienes (LTs) -the products of arachidonic acid metabolism. The goal of this systematic review, performed in line with the PRISMA statement, was to investigate the potential role of LTs in the pathophysiology of atherosclerotic cardiovascular diseases (CVD). Material and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Recently, Wachsmann et al [ 74 , 75 ] emphasized the importance of diabetes control and HbA1C in the favorable evolution one year after endovascular treatment in patients diagnosed with critical limb ischemia; much more recently in 2022, they published a systematic review in which they demonstrated the role of leukotrienes in cardiovascular atherosclerotic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wachsmann et al [ 74 , 75 ] emphasized the importance of diabetes control and HbA1C in the favorable evolution one year after endovascular treatment in patients diagnosed with critical limb ischemia; much more recently in 2022, they published a systematic review in which they demonstrated the role of leukotrienes in cardiovascular atherosclerotic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Among the inflammatory markers studied in the context of atherosclerosis, Wachsmann-Maga et al explored the role of leukotrienes (LTs), suggesting the potential for a pathophysiological link between atherosclerotic alterations and products derived from the metabolism of arachidonic acid [70]. Leukotrienes (LTs) are highly potent biologically active compounds that play a role in various cellular processes and function as mediators of inflammation.…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…Leukotrienes (LTs) are highly potent biologically active compounds that play a role in various cellular processes and function as mediators of inflammation. They belong to the eicosanoid group, which are signaling molecules involved in inflammation [70]. LTs are produced as part of the metabolic pathway that oxidizes essential fatty acids, such as arachidonic acid (AA) and eicosatetraenoic acid (EPA), through the action of the enzyme arachidonate 5-lipoxygenase.…”
Section: Inflammatory Markersmentioning
confidence: 99%
See 2 more Smart Citations